Epstein–Barr Virus Infection and Posttransplant Lymphoproliferative Disorder. Issue 3 (24th January 2013) - Green, M.; Michaels, M. G.
<x xml:space="preserve">Abstract</x> Epstein–Barr virus (EBV) is an important pathogen in recipients of solid organ transplants (SOT). Infection with EBV manifests as a spectrum of diseases/malignancies ranging from asymptomatic viremia through infectious mononucleosis to posttransplant lymphoproliferative disorder (PTLD). EBV disease and its associated PTLD is more frequently seen when primary EBV infection occurs after transplant, a common scenario in pediatric SOT recipients. Intensity of immunosuppressive therapies also influences the risk for PTLD. The use of EBV viral load monitoring facilitates the diagnosis and management of EBV/PTLD as well as being used to inform preemptive therapy with reduction of immunosuppression, the most effective intervention for prevention of and treatment for PTLD. Other therapies, including the rituximab (anti‐CD20 monoclonal antibody) and traditional chemotherapy, are also useful in the treatment of established PTLD. The future development of standards for management based on EBV viral load and routine monitoring of EBV‐specific CTL responses promise further improvement in outcomes with EBV and PTLD.